FOSTERING INNOVATION PERFORMANCE OF SMES IN CULINARY SECTOR - Ilhami, Susanti Dwi; Damayanti, Damayanti (Business Management Analysis Journal (BMAJ), 2024)
The quantitative research that has been carried out aims to explore the role of absorptive capacity as a mediator and risk taking as a moderator in the influence of entrepreneurial leadership, knowledge search, and innovation performance in Culinary SMEs in Rembang Regency. The sampling technique was carried out using purposive sampling of 82 respondents. Data analysis was carried out using the SEM-PLS method. The research results reveal that knowledge search and absorptive capacity have a significant effect on innovation performance. However, entrepreneurial leadership does not have a significant effect on innovation performance. Apart from that, absorptive capacity is proven to only play a mediating role in the influence of knowledge search on innovation performance. The next valuable finding namely risk taking is unable to moderate this influence. This research indicates that Rembang Regency Culinary SMEs can use research findings as a reference for increasing innovation performance by using absorptive capacity and knowledge search.